The Evolution of Distributed Systems: Architectural Developments, Technologies, and Modern Computing Challenges: Evolusi Sistem Terdistribusi: Perkembangan Arsitektur, Teknologi, dan Tantangan Komputasi Modern - Geby Putri Maharani; Rahmaniar Rahmaniar (WITECH: Jurnal Teknologi Rekayasa Komputer dan Jaringan, 2026)
This study examines the evolution of distributed systems by analyzing architectural changes, technological transitions, and emerging challenges in modern computing environments. The research applies a Systematic Literature Review (SLR) approach to ensure a structured and transparent review process. Literature was collected from two main academic databases, namely Scopus and Google Scholar, using keywords such as “distributed systems evolution”, “cloud computing architecture”, “service-oriented architecture”, “microservices”, and “cloud-native systems”. The initial search identified 50 relevant publications published between 2015 and 2025. After applying inclusion and exclusion criteria based on relevance, publication year, and scientific credibility, 25 articles were selected for further analysis. The selected studies were synthesized using thematic analysis to identify recurring themes, development phases, and major challenges in distributed systems. The findings reveal that distributed systems have evolved from client–server models to service-oriented architecture (SOA), followed by cloud computing and cloud-native microservices. This transformation is mainly driven by the increasing need for scalability, flexibility, fault tolerance, and real-time processing. However, the transition toward highly modular and decentralized systems also introduces new challenges, particularly in system complexity, security, data consistency, and operational management.